Hubungan Pengetahuan, Sikap, Umur, dan Keterampilan Dasar dengan Penggunaan Alat Pelindung Diri pada Pekerja Laundry di Kota Kupang - Suyitro Seme; Yendris K. Syamruth; Afrona E. L. Takaeb (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Laundry is a necessity for some people who have a busy schedule so they don't have more time to wash clothes. However, there are still many laundry entrepreneurs who do not pay attention to the work safety of employees so that work accidents cannot be avoided. The lack of awareness to constantly use PPE is influenced by many factors. This study aims to determine the relationship between knowledge, attitudes, age and basic skills with the use of PPE in laundry workers in Kupang City. The research method used was cross sectional with a population of 83 people and the number of samples used was 46 people with a random sampling method. The instrument of this study is a questionnaire. Data analysis using chi-square. The results showed that there was a relationship between independent variables and dependent variables using the Chi-square test, so the results obtained were that there was a relationship between the use of PPE in laundry workers in Kupang City with knowledge (p = 0.21), attitude (p = 0.000), age (0.029) and basic skills (p = 0.000). Based on the keofesien (r) test of the four variables, it has a very low correlation or relationship linkage. Where the first variable is the keofesien test value (r) of 0.019, the second variable is 0.000, the third variable is 0.013 and the fourth variable is 0.000 with the use of correlational analysis from this study is r = -1 or close to -1 so that the relationship between the two variables is strong and has the opposite relationship. It is hoped that laundry owners can provide a correct understanding of the importance of using PPE when working to avoid the risk of work accidents.